(untitled) (Journal of Dissability Studies and Research (JDSR), 2023)
Inclusive education in Indonesia still has obstacles. The obstacles that has occurred so far is the teacher’s lack of knowledge about children with special needs. The teacher’s lack of skill in dealing with the students and the teacher’s attitude towards the students, which can be seen as looking down on them. This creates encouragement for educational institution to be able to provide inclusive education evenly and variedly, regardless of the differences between regular children and those with special needs. This articles aims to describe the implementation of inclusive education. This type of research is library research using analytical descriptive method by looking for primary and secondary references realted to this study it is known that the principles of implementing inclusive education include the principles of equality and improving the quality of various learning methods that can provide access for all children and respect differences.